Stroke Incidence Following Traumatic Brain Injury in Older Adults. Issue 2 (March 2015) - Albrecht, Jennifer S.; Liu, Xinggang; Smith, Gordon S.; Baumgarten, Mona; Rattinger, Gail B.; Gambert, Steven R.; Langenberg, Patricia; Zuckerman, Ilene H.
Abstract : Objective: Following traumatic brain injury (TBI), older adults are at an increased risk of hemorrhagic and thromboembolic events, but it is unclear whether the increased risk continues after hospital discharge. We estimated incidence rates of hemorrhagic and ischemic stroke following hospital discharge for TBI among adults 65 years or older and compared them with pre-TBI rates. Participants: A total of 16 936 Medicare beneficiaries 65 years or older with a diagnosis of TBI in any position on an inpatient claim between June 1, 2006, and December 31, 2009, who survived to hospital discharge. Design: Retrospective analysis of a random 5% sample of Medicare claims data. Main Measures: Hemorrhagic stroke was defined as ICD-9 ( International Classification of Diseases, Ninth Revision ) codes 430.xx-432.xx. Ischemic stroke was defined as ICD-9 codes 433.xx-435.xx, 437.0x, and 437.1x. Results: There was a 6-fold increase in the rate of hemorrhagic stroke following TBI compared with the pre-TBI period (adjusted rate ratio, 6.5; 95% confidence interval, 5.3-7.8), controlling for age and sex. A smaller increase in the rate of ischemic stroke was observed (adjusted rate ratio, 1.3; 95% CI, 1.2-1.4). Conclusion: Future studies should investigate causes of increased stroke risk post-TBI as well as effective treatment options to reduce stroke risk and improve outcomes post-TBI among older adults.